The Impact of Contextual and Emotional E-Wallet Personalization on MSME Satisfaction in Medan - Gracello Febry Christanto; Erwin Setiawan Panjaitan (Brilliance: Research of Artificial Intelligence, 2025)
This thesis investigates the influence of personalization features in e-wallet applications on user satisfaction among Micro, Small, and Medium Enterprises (MSMEs) in Medan City. Using the DeLone and McLean Information System Success Model (2003) as the theoretical foundation, this study highlights the importance of aligning system functions with the specific characteristics and conditions of individual users, especially within the dynamic context of MSMEs. The research introduces a novel approach to personalization by focusing on contextual and emotional dimensions, where e-wallet systems adapt to user conditions such as time of transaction, frequency of usage, and behavioral financial patterns. Unlike conventional personalization, which primarily targets content or interface, contextual-emotional personalization considers psychological nuances and daily financial habits, aiming to create a more human-centered and adaptive digital experience. The study employs a quantitative approach through the distribution of structured questionnaires to 200 MSME respondents who actively use e-wallets in their business operations. Data collected was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results demonstrate that contextual and emotional personalization has both direct and indirect effects on user satisfaction through intermediary variables such as system quality, information quality, and service quality. These findings offer practical implications for digital financial service providers aiming to improve user experience and strengthen system engagement. Additionally, the research contributes to the academic discourse by extending the DeLone and McLean model into new areas of emotional and contextual adaptability in information systems.